Pelton Turbines - Zhang, Zhengji (Springer International Publishing : Imprint: Springer, 2016)
This book concerns the theoretical foundations of hydromechanics of Pelton turbines from the engineering viewpoint. For reference purposes, all relevant flow processes and hydraulic aspects in a Pelton turbine have been analyzed completely and systematically. The analyses especially include the quantification of all possible losses existing in the Pelton turbine and the indication of most available potential for further enhancing the system efficiency. As a guideline the book therefore supports further developments of Pelton turbines with regard to their hydraulic designs and optimizations. It is thus suitable for the development and design engineers as well as those working in the field of turbo machinery. Many laws described in the book can also be directly used to simplify aspects of computational fluid dynamics (CFD) or to develop new computational methods. The well-executed examples help better understand the related flow mechanics.